Pengembangan Model Evaluasi Pembelajaran Pendidikan Kewarganegaraan Berbasis Kurikulum Merdeka di Madrasah - Muhammad Nurman (Universitas Hamzanwadi, 2023)
This study aims to produce a product model for evaluating civic education learning based on the independent curriculum. The research method uses the Research and Development (R&D) approach with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research was conducted at Madrasah Aliyah involving civic education teachers and students. Data collection methods used observation, interviews, and questionnaires. The collected data were analyzed using quantitative and qualitative analysis techniques, namely descriptive analysis, inferential analysis, and covariance analysis. Qualitative analysis, namely data from interviews and observations were analyzed qualitatively using thematic analysis techniques. Triangulation was used to determine the credibility of the research results, namely triangulation of data sources (teachers, students, experts) and triangulation of methods. The research data were analyzed quantitatively and qualitatively. The results of the study indicate that the main problems in evaluating civic education learning in the implementation of the independent curriculum include the dominance of cognitive assessments, the lack of authentic assessments, and suboptimal measurement of the Pancasila student profile dimensions. The developed civic education learning evaluation model has the following characteristics: (a) comprehensively measuring the dimensions of civic knowledge, skills, and character; (b) using diverse and authentic assessment techniques, especially projects and portfolios; (c) integrating formative and summative assessments; and (d) oriented towards the development of Pancasila student profiles. The project- and portfolio-based civic education learning evaluation model with the integration of continuous formative assessment can improve students' critical thinking skills by 45% and civic skills by 30% compared to conventional evaluation models. The developed evaluation model received high validation (a score of 4.74 out of 5) from curriculum and civic education learning experts, as well as a good level of practicality (a score of 4.30 out of 5) based on teacher assessments.